Gendered selection trait preferences for farmed fish in Egypt - Murphy, Seamus (WorldFish, 2018)
Presented by Seamus Murphy (WorldFish), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.